2021
DOI: 10.3390/agronomy12010052
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Sap Flow Measurements to Assess the Water Requirements of Three Australian Native Tree Species

Abstract: The measurement of sap movement in xylem sapwood tissue using heat pulse velocity sap flow instruments has been commonly used to estimate plant transpiration. In this study, sap flow sensors (SFM1) based on the heat ratio method (HRM) were used to assess the sap flow performance of three different tree species located in the eastern suburbs of Melbourne, Australia over a 12-month period. A soil moisture budget profile featuring potential evapotranspiration and precipitation was developed to indicate soil moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Various scientific studies on tree transpiration have been performed using SFM1 because it can accurately measure tree water use [4,17,18,19,20]. One benefit of utilizing SFM1 is its ability to be deployed on-site without first calibrating the sensors.…”
Section: Sap Flow Sensorsmentioning
confidence: 99%
“…Various scientific studies on tree transpiration have been performed using SFM1 because it can accurately measure tree water use [4,17,18,19,20]. One benefit of utilizing SFM1 is its ability to be deployed on-site without first calibrating the sensors.…”
Section: Sap Flow Sensorsmentioning
confidence: 99%
“…Previous studies indicated that R s and VPD are the main factors that influence transpiration in a single tree in terms of meteorological factors affecting plant sap flow ( Deng et al, 2021 ). Another study indicated that solar radiation is the maximum impact factor and potential evapotranspiration and solar radiation are positively correlated with relative changes in the sap flow volume of plants with an R 2 of 0.75 ( Sun et al, 2021 ). However, the degree of influence of meteorological factors on sap flow varies for different moisture conditions.…”
Section: Introductionmentioning
confidence: 99%